Attitudinal Meaning in Literary Texts: An Appraisal Analysis of the Translation of the Novel Magdalena from Arabic into Indonesian - Nurul Aini Choiriyah; Doni Jaya (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2025)
This study analyzed the attitudinal meaning in the novel Magdalena by Mustafa Lutfi al-Manfaluthi, particularly after its translation from Arabic to Indonesian. As an appraisal analysis, the research aimed to identify categories of attitude, including 1) affect, 2) judgement, and 3) appreciation, and explored the translation techniques applied to these elements. This qualitative case study used a descriptive approach to examine shifts in attitudinal meaning through comparisons between the source and target texts. The results indicated that 1) negative affect dominated the characterization of the main character, Magdalena, and 2) modulation was the most frequently used translation technique, allowing for cultural adaptation without losing emotional meaning. In conclusion, the modulation technique played a crucial role in preserving the attitude and emotional intensity aligned with the Indonesian cultural context, ensuring that the literary text’s messages and values were effectively conveyed. This research contributed to translation studies, especially in analyzing attitude and translation technique choices that influenced readers’ perception.